Pengaruh Pengetahuan Perpajakan, Sanksi Perpajakan, dan Kesadaran Wajib Pajak Terhadap Kepatuhan Pelaporan WPOP Pada KPP Pratama Tabanan - Susanti, Ni Kadek Nia; Kusumawati, Ni Putu Ayu; Ayu, Putu Cita (UNHI Press, 2025)
This time taxes have a very important contribution to the progress of a country. The realization of compliance with taxpayer reporting in reporting Annual Tax Returns (SPT) has decreased. The impact of cases of tax officials with big assets, has made some parties distrustful and even called for not paying taxes. In several areas, the ratio of individual taxpayer reporting compliance has decreased as has happened at KPP Pratama Tabanan. This is caused by factors such as tax knowledge, tax sanctions and taxpayer awareness. The aim of this research is to determine the effect of tax knowledge, tax sanctions and taxpayer awareness on individual taxpayer reporting compliance. The data analyzed was primary data through distributing questionnaires distributed to 100 individual taxpayers registered at KPP Pratama Tabanan 2022. Determining the sample size for this study used simple random sampling and the Slovin formula. Statistical testing in testing hypotheses using the SPSS version 24.0 program test tool. The results of this study show that: individually, Tax Knowledge, Tax Sanctions, and Taxpayer Awareness has a positive and significant effect on Individual Taxpayer Reporting Compliance.